2021
DOI: 10.1002/cam4.4465
|View full text |Cite
|
Sign up to set email alerts
|

Improved risk prediction of chemotherapy‐induced neutropenia—model development and validation with real‐world data

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…To develop computational models for predicting the probability of surviving 180 days of csDMARD therapy without laboratory abnormalities, we applied Lasso penalized Cox proportional hazards regression together with stable iterative variable selection (SIVS) to the data in the training cohort to identify the most influential variables on the outcome and to develop a simple-to-use computational model for clinical use 13 . Previously, penalized regression with SIVS has been reported to be an effective method for developing accurate, well-generalizable models with minimum number of variables 14 , 15 . In SIVS, model training with fivefold cross-validation was repeated 100 times.…”
Section: Methodsmentioning
confidence: 99%
“…To develop computational models for predicting the probability of surviving 180 days of csDMARD therapy without laboratory abnormalities, we applied Lasso penalized Cox proportional hazards regression together with stable iterative variable selection (SIVS) to the data in the training cohort to identify the most influential variables on the outcome and to develop a simple-to-use computational model for clinical use 13 . Previously, penalized regression with SIVS has been reported to be an effective method for developing accurate, well-generalizable models with minimum number of variables 14 , 15 . In SIVS, model training with fivefold cross-validation was repeated 100 times.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with neutropenia are generally more susceptible to infections and sepsis (Nesher and Rolston, 2013;Kochanek et al, 2019). There are many studies which have identified risk factors for neutropenia through the use of machine learning (Cho et al, 2020;Venäläinen et al, 2021;Wiberg et al, 2021). Machine learning uses algorithms in order to uncover possible relationships between variables in a dataset.…”
Section: Introductionmentioning
confidence: 99%